2020
DOI: 10.1126/scisignal.aba8627
|View full text |Cite
|
Sign up to set email alerts
|

A PI3K- and GTPase-independent Rac1-mTOR mechanism mediates MET-driven anchorage-independent cell growth but not migration

Abstract: Receptor tyrosine kinases (RTKs) are often overexpressed or mutated in cancers and drive tumor growth and metastasis. In the current model of RTK signaling, including that of MET, downstream phosphatidylinositol 3-kinase (PI3K) mediates both cell proliferation and cell migration, whereas the small guanosine triphosphatase (GTPase) Rac1 mediates cell migration. However, in cultured NIH3T3 and glioblastoma cells, we found that class I PI3K mediated oncogenic MET–induced cell migration but not anchorage-independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
(91 reference statements)
1
12
0
Order By: Relevance
“…Moreover, when analyzing Rac1 activity in an anchorage-independent growth (AIG) assay to mimic cell behavior in the absence of substrate adhesion, we observed activated Rac1 in suspension which we could readily inhibit using NSC 23766 after 4 h and 24 h of treatment, respectively (see Figures 3C and 3Di, average cluster size of 75 ± 4 mm; Figure S3E; Video S5). This is in line with Rac1 and other GTPases playing an active role in AIG and cancer cell survival in transit (Follain et al, 2020;Hervieu et al, 2020;Vennin et al, 2017). Interestingly, the outer versus inner cells of AIGs were further assessed, and while cells on the periphery of clusters were inherently more inactive than cells within the center of the cluster, they were also more readily inactivated by treatment with Rac1 inhibition than cells on the inside (Figure 3Dii).…”
Section: Rac1 Inhibition Enhances Vulnerability To Fluid-flowinduced Shear Stress and Results In Decreased Dissemination And Invasion Of supporting
confidence: 71%
“…Moreover, when analyzing Rac1 activity in an anchorage-independent growth (AIG) assay to mimic cell behavior in the absence of substrate adhesion, we observed activated Rac1 in suspension which we could readily inhibit using NSC 23766 after 4 h and 24 h of treatment, respectively (see Figures 3C and 3Di, average cluster size of 75 ± 4 mm; Figure S3E; Video S5). This is in line with Rac1 and other GTPases playing an active role in AIG and cancer cell survival in transit (Follain et al, 2020;Hervieu et al, 2020;Vennin et al, 2017). Interestingly, the outer versus inner cells of AIGs were further assessed, and while cells on the periphery of clusters were inherently more inactive than cells within the center of the cluster, they were also more readily inactivated by treatment with Rac1 inhibition than cells on the inside (Figure 3Dii).…”
Section: Rac1 Inhibition Enhances Vulnerability To Fluid-flowinduced Shear Stress and Results In Decreased Dissemination And Invasion Of supporting
confidence: 71%
“…TIPE2 can directly bind and inhibit Rac ( 39 ), which was confirmed in TIPE2-overexpressed NK92 cells (data not shown). Rac1 was previously shown to directly bind mTOR and mediate localization of mTORC1 and mTORC2 to specific membranes for their activation ( 50 ), and inhibition or deletion of Rac suppresses mTOR activity independently of PI3K ( 50 53 ). Therefore, TIPE2 might suppress mTOR activation by inhibiting Rac1.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that Rac1 can form a complex with mTOR to promote its transport to the plasma membrane (23).…”
Section: Rac1/cdc42 Can Regulate the Expression Of Mtormentioning
confidence: 99%